Urgensi Literasi Keuangan dan Motivasi Berinvestasi dalam Meningkatkan Minat Investasi Mahasiswa - Ima Karima; Krisnawati Setyaningrum Nugraheni (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of financial literacy and investment motivation on students' investment interest. With the growing development of the capital market in Indonesia and the variety of investment instruments available, it is important for the younger generation, especially students, to have a good understanding of financial and investment concepts from an early age. This study used a quantitative approach with a survey method of 100 students from various universities. Data were collected through a questionnaire that measured respondents' levels of financial literacy, investment motivation, and investment interest. The results showed that financial literacy (β = 0.132, p < 0.001) and investment motivation (β = 0.805, p < 0.001) had a positive and significant effect on students' investment interest. Together, the two variables explained 81.0% of the variation in students' investment interest (R² = 0.810). The implication of this study is the need to strengthen financial education programs in universities and develop investment outreach programs to increase the participation of the younger generation in investment activities.